2013
DOI: 10.1063/1.4794335
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic interactions and reversal mechanisms in Co nanowire and nanotube arrays

Abstract: Ordered hexagonal arrays of Co nanowires (NWs) and nanotubes (NTs), with diameters between 40 and 65 nm, were prepared by potentiostatic electrodeposition into suitably modified nanoporous alumina templates. The geometrical parameters of the NW/NT arrays were tuned by the pore etching process and deposition conditions. The magnetic interactions between NWs/NTs with different diameters were studied using first-order reversal curves (FORCs). From a quantitative analysis of the FORC measurements, we are able to o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
60
0
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 97 publications
(70 citation statements)
references
References 42 publications
7
60
0
3
Order By: Relevance
“…It was shown that, thanks to their hollow structure, NTs present lower magnetic interactions compared with the same diameter and same density NWs [9,45,49]. It was further indicated that the physical reason of low exchange energy in NTs was the absence of curling related vortices which are present in other magnetic structures.…”
Section: M Smentioning
confidence: 96%
See 2 more Smart Citations
“…It was shown that, thanks to their hollow structure, NTs present lower magnetic interactions compared with the same diameter and same density NWs [9,45,49]. It was further indicated that the physical reason of low exchange energy in NTs was the absence of curling related vortices which are present in other magnetic structures.…”
Section: M Smentioning
confidence: 96%
“…Nevertheless, the structural, magnetic, and magnetization Switching field distribution of the medium before and after magnetostatic field correction. Reprinted with permission from [36] reversal properties of ferromagnetic NTs were investigated experimentally as a function of their geometrical parameters by other magnetometry techniques [9,15,25,45,46,50,65]. In multisegmented nanocylinders, with alternating magnetic wires and tubes segments, it was shown that the NT segments switch their magnetization before the NWs resulting in a trapped domain wall between the two segments [51].…”
Section: M Smentioning
confidence: 99%
See 1 more Smart Citation
“…Nanoporous anodic Al 2 O 3 films, obtained by the simple and inexpensive technique for two-step anodization of high-purity Al substrates (Masuda and Fukuda, 1995;Masuda and Satoh, 1996), have attracted huge interest and have been used as templates for the synthesis of a wide range of nanomaterials (Eftekhari, 2008;Lupu, 2010;Nalwa, 2011), including ordered arrays of magnetic nanowires Vázquez et al, 2005;Prida et al, 2007;Klammer et al, 2010), nanoparticles (Gultepe et al, 2007;Badini et al, 2011), nanotubes (Imai et al, 1999;Daub et al, 2007;Zierold et al, 2011;Proença et al, 2013) arrays of antidots (Masuda and Fukuda, 1995;Vázquez et al, 2008;López-Antón et al, 2009;Béron et al, 2011;Merazzo et al, 2012). Anodization of Al consists of the anodic oxidation of an Al electrode under wellcontrolled electrochemical conditions.…”
Section: Mild Anodizationmentioning
confidence: 98%
“…The opening of the pores was performed by floating the sample in phosphoric acid, which led to a small enlargement of the final pore diameter to $40 nm. 28 For the subsequent potentiostatic electrodeposition of Co NTs inside the pores, an Au metallic contact of $50 nm was sputtered at the pores' opened ends to serve as the working electrode during deposition. 29 A Pt mesh and Ag/AgCl (in 4 M KCl) were used as counter and reference electrodes, respectively.…”
Section: Methodsmentioning
confidence: 99%